Laminar Source Flow of Second Order Fluid Between two Parallel Coaxial Disks Rotating at Different Speeds - Chaudhary, R. C.; Rajvanshi, S. C. (Defence Science Journal, 2014)
The laminar source flow of second order fluid between two infinite parallel disks rotating with different velocities has been studied in this paper. The solution has been obtained by double series expansion about a known solution at a large radius. The effect of non-Newtonian parameters has been discussed on velocity profiles for small rotational Taylor numbers of the disks.